2012
DOI: 10.4049/jimmunol.1102795
|View full text |Cite
|
Sign up to set email alerts
|

Profound Depletion of Host Conventional Dendritic Cells, Plasmacytoid Dendritic Cells, and B Cells Does Not Prevent Graft-versus-Host Disease Induction

Abstract: The efficacy of alloSCT is limited by graft-versus-host disease (GVHD). Host hematopoietic antigen presenting cells (APCs) are important initiators of GVHD making them logical targets for GVHD prevention. Conventional dendritic cells (cDCs) are key APCs for T cell responses in other models of T cell immunity and they are sufficient for GVHD induction. However, we report here in two polyclonal GVHD models in which host hematopoietic APCs are essential, that GVHD was not decreased when recipient cDCs were induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 47 publications
(82 reference statements)
5
60
0
1
Order By: Relevance
“…Shlomchik et al recently demonstrated that selective depletion of host DCs did not ameliorate GVHD. 42 It has been shown that uptake of apoptotic cells by DCs induces Tregs, which when triggered by specific antigens, can act back via a "feedback loop" on immature DCs to further block the upregulation of costimulatory molecules. Additionally, Tregs are able to directly inhibit T-cell activation by inhibition of CD28 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Shlomchik et al recently demonstrated that selective depletion of host DCs did not ameliorate GVHD. 42 It has been shown that uptake of apoptotic cells by DCs induces Tregs, which when triggered by specific antigens, can act back via a "feedback loop" on immature DCs to further block the upregulation of costimulatory molecules. Additionally, Tregs are able to directly inhibit T-cell activation by inhibition of CD28 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Recent data have indicated that both host hematopoietic or nonhematopoietic APCs, in the absence of one or another, can activate donor T cells and induce GVHD. 18,19,21 Furthermore, the elimination of specific hematopoietic APC subsets, such as DCs or macrophages, may aggravate GVHD, suggesting that these cells may play a role in controlling GVHD. 18,20,22,44 These observations, taken in light of our data, suggest that the negative regulatory pathways of professional APCs, DCs, or macrophages, might be critical for reducing GVHD severity following its induction by the activation of donor T cells by the DAMP/PAMP activated host APCs.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly critical in light of the recent observations, which demonstrate that the absence of any one subset of professional host-derived hematopoietic APCs, such as DCs or macrophages, contrary to the expectations of reducing donor T-cell responses, are either irrelevant, or actually enhance donor T-cell responses and accentuate GVHD severity. [18][19][20][21][22] These newer observations suggest that pathways that mitigate the hematopoietic APCs may be as critical for attenuating GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…CD24 is broadly expressed in hematopoietically derived cells, immature neuronal cells, and epithelial cells (26). Given the complexity and number of cell types involved in inducing and amplifying GVHD, whether Siglec expression on donor or host B cells or other cells will affect acute GVHD remains to be explored (27,28).…”
Section: Discussionmentioning
confidence: 99%